Managing Training for Civil Servants with Planning Roles in Indonesia: Lessons from Singapore - Feita Puspita Murti (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2020)
Indonesia is a developing country that is vigorously seeking to boost its economic growth. One of the nine programs to encourage national development is to improve the quality of civil servants, to strengthen the capacity for policy design and implementation in ministries and institutions, and hence to improve public service delivery. Some researchers argue that many developing countries have attempted to improve civil service training but only a few have succeeded to make significant contributions to strengthening their institutions. A group of researchers has identified ten factors that they regard as critical for training management effectiveness which have been applied in the Singapore civil service training institutions. The researchers suggest that the same factors may be important for developing countries. This study attempts to evaluate the potential application of the ten critical factors affecting training management effectiveness for Indonesian civil service training institutions. To do this, the thesis presents a comparative analysis of training management in Indonesia and Singapore. In this ‘lens’ of comparison, the Singapore model is used as a framework to understand the training management model in Indonesia. Based on the findings, nine out of ten factors could be implemented in the Indonesian model. However, factors related to the political context are likely to be challenging, as the political environment in the developed and developing countries are somewhat different.